2019
DOI: 10.1007/s00192-019-04162-x
|View full text |Cite
|
Sign up to set email alerts
|

Razor-type dermatomes enable quick and thin vaginal dissection with less bleeding in colpocleisis

Abstract: Introduction and hypothesis Although colpocleisis is a low-invasive surgical option to treat pelvic organ prolapse, it sometimes involves a long operative time with substantial bleeding. To streamline the vaginal dissection process in colpoclesis, we introduced the usage of dermatomes. Methods All patients were sexually inactive women with post-hysterectomy prolapse. Data of the dermatome group were retrospectively compared with those of the historical control group based on operative features, perioperative c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Anatomical success defined as POP-Q stage ≤1 ranged from 62.5% to 100% [ 7 , 12 , 15 , 24 , 26 , 29 , 43 ]. Eisenberg et al reported an anatomical success rate of 62.5% (POP-Q ≤1), but the success rate increased to 100% when they extended the definition to POP-Q ≤2 [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Anatomical success defined as POP-Q stage ≤1 ranged from 62.5% to 100% [ 7 , 12 , 15 , 24 , 26 , 29 , 43 ]. Eisenberg et al reported an anatomical success rate of 62.5% (POP-Q ≤1), but the success rate increased to 100% when they extended the definition to POP-Q ≤2 [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Only a few authors have addressed regret over the loss of sexual function. No regret regarding coital ability was reported by many studies [ 1 , 7 , 11 , 18 , 22 , 25 , 35 , 43 ], but coital regret was reported too: from 1.15% to 12.9% [ 17 , 23 , 32 , 37 ]. In a study by Fitzgerald et al, 3% (2 out of 79), 87% (69 out of 79), and 10% of the women (8 out of 79) reported “worse,” “the same,” or “better” sexual function respectively, after 1 year of follow-up [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, difficulties in dissection or tissue handling increase the incidence of intraoperative complications such as bladder/visceral injury, bleeding and so on [ 10 , 11 ]. In particular, in cases with post-hysterectomy prolapse, the vaginal wall tends to be thin; thus, vaginal dissection becomes difficult, and unintended opening of the peritoneum may occur [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are very few published studies on interventions to reduce blood loss during vaginal prolapse surgery. In a study on colpoclesis razor dermatome dissection was found to be faster and associated with lesser bleeding among women undergoing colpoclesis for prolapse [16].…”
mentioning
confidence: 95%